THE EFFECT OF SERVICE QUALITY, PRICE AND PLACE ON REPURCHASE INTEREST THROUGH CONSUMER SATISFACTION AT CV LINA FAKHIRAH - Husna, Saadatul; Pardiman; Nur Hidayati (International Journal of Cultural and Social Science, 2025)
Study This aim For analyze influence quality service , price , and place to interest buy repeat through satisfaction customer at CV Lina Fakhirah , one perpetrator business retail in the District Tebing Tinggi. The method used is quantitative with distribution questionnaire to 100 respondents who were CV Lina Fakhirah consumers . Data processing is carried out using equation model Structural Modeling (SEM) based on Partial Least Square (PLS). The research results show that variables price and place influential significant to satisfaction customers , whereas quality service No influential significant . In terms of directly , only variables influential place? significant to interest buy repeat . On the other hand , satisfaction customer proven own influence significant to interest buy repeat as well as mediate connection between price and place to interest buy repeat . However , the influence No direct quality service through satisfaction to interest buy repeat No significant . Research model This own Power very strong prediction with R² value of 90.4% for interest buy repeat and 77.7% for satisfaction customers , as well as Q² value of 0.979. Findings This emphasize that competitive pricing strategy and location? strategic shop? own role dominant in form loyalty customers . On the other hand , quality service need improvement in order to be able to give contribution significant to satisfaction and interest buy repeat . Implications in practice , the perpetrator business retail need prioritize development aspect price and location , as well as create experience satisfying shopping? For increase loyalty customer . Keywords : quality? service , price , place , satisfaction customers , interests buy repeat , CV Lina Fakhirah